USING TWO FEEDBACK TYPES AND THEIR IMPACT ON PERFORMANCE AND MEASURING DEVELOPMENT RATIO OF BASKETBALL BASIC SKILLS - Ali Qutaiba Younus (Universitas Negeri Jakarta, 2025)
Background. Feedback is a critical element in sports skill acquisition, directly influencing learning efficiency and performance quality. In basketball, immediate feedback and reinforcement feedback may differently affect the mastery of basic skills. Objective. This study aimed to examine the impact of immediate feedback and reinforcement feedback on learning selected basic basketball skills, to compare post-test results between the two feedback types, and to analyze the development ratio for each skill. Methods. An experimental design was employed involving first-year middle school students at Fayda Secondary School for Boys (academic year 2024–2025). From a population of 166 students, 40 were randomly selected and divided into two experimental groups (n=20 each). Group 1 received immediate feedback, while Group 2 received reinforcement feedback. The training lasted eight weeks, with two 45-minute sessions per week. Skills assessed included chest pass, long pass, free throw, and tapping. Pre- and post-tests measured performance and development ratios. Results. Both feedback types significantly improved skill performance. No significant difference emerged between groups in chest pass and long pass performance. However, Group 2 (reinforcement feedback) outperformed Group 1 in free throw and tapping. Development ratios were high in all skills, with minimal difference between groups for chest pass and long pass, but a marked advantage for Group 2 in free throw and tapping. Conclusions. Both immediate and reinforcement feedback positively influence basketball skill learning, with reinforcement feedback showing greater benefits for more complex skills. The findings highlight the value of tailored feedback strategies in youth basketball training and provide evidence-based recommendations for coaching practices.